Silver Linings Reported by Australians Experiencing Public Health Restrictions during the First Phase of the COVID-19 Pandemic: A Qualitative Report - Narelle Campbell (MDPI AG, 2021)
This national study investigated the positives reported by residents experiencing the large-scale public health measures instituted in Australia to manage the first wave of the COVID-19 pandemic in 2020. Most Australians had not previously experienced the traditional public health measures used (social distancing, hand hygiene and restriction of movement) and which could potentially impact negatively on mental well-being. The research design included qualitative semi-structured phone interviews where participants described their early pandemic experiences. Data analysis used a rapid identification of themes technique, well-suited to large-scale qualitative research. The ninety participants (mean age 48 years; 70 women) were distributed nationally. Analysis revealed five themes linked with mental well-being and the concept of silver linings: safety and security, gratitude and appreciation, social cohesion and connections, and opportunities to reset priorities and resilience. Participants demonstrated support for the public health measures and evidence of individual and community resilience. They were cognisant of positives despite personal curtailment and negative impacts of public health directives. Stories of hope, strength, and acceptance, innovative connections with others and focusing on priorities and opportunities within the hardship were important strategies that others could use in managing adversity.